2017
DOI: 10.1186/s13613-017-0289-y
|View full text |Cite
|
Sign up to set email alerts
|

Can proportional ventilation modes facilitate exercise in critically ill patients? A physiological cross-over study

Abstract: BackgroundEarly exercise of critically ill patients may have beneficial effects on muscle strength, mass and systemic inflammation. During pressure support ventilation (PSV), a mismatch between demand and assist could increase work of breathing and limit exercise. A better exercise tolerance is possible with a proportional mode of ventilation (Proportional Assist Ventilation, PAV+ and Neurally Adjusted Ventilatory Assist, NAVA). We examined whether, in critically ill patients, PSV and proportional ventilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Proportional assist ventilation (PAV) [10] and neurally adjusted ventilatory assist (NAVA) [11] are designed to improve patient–ventilator interaction [12]. Both modes are designed to adjust inspiratory pressure proportionally to the patient’s inspiratory demand and are known as proportional modes [13]. PAV+ (Puritan Bennett 840/980 ventilator; Covidien, Boulder, Colorado, USA) automatically measures the elastance and resistance of the respiratory system during spontaneous breathing and delivers the adequate pressure needed to meet the flow and volume demand that are instantaneously measured on a breath-to-breath basis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Proportional assist ventilation (PAV) [10] and neurally adjusted ventilatory assist (NAVA) [11] are designed to improve patient–ventilator interaction [12]. Both modes are designed to adjust inspiratory pressure proportionally to the patient’s inspiratory demand and are known as proportional modes [13]. PAV+ (Puritan Bennett 840/980 ventilator; Covidien, Boulder, Colorado, USA) automatically measures the elastance and resistance of the respiratory system during spontaneous breathing and delivers the adequate pressure needed to meet the flow and volume demand that are instantaneously measured on a breath-to-breath basis [14].…”
Section: Introductionmentioning
confidence: 99%
“…These results could be explained by a lack of knowledge on the optimal dosage of physical therapy for ICU patients (in terms of intensity, duration and frequency) 18–21. Alternatively, during physical therapy a mismatch between ventilatory support and exercise-induced ventilatory demand may excessively increase work of breathing, limiting physical therapy performance and eventually leading to fatigue 22…”
Section: Introductionmentioning
confidence: 99%
“…Despite expert consensus and recommendations on active mobilisation of mechanically ventilated patients,23 ventilator settings and safety parameters to monitor during mobilisation have not yet been defined. Some authors have suggested strategies to adjust ventilatory support during physical therapy; for example, increasing support level during pressure support ventilation,24 using proportional ventilation modes,22 employing assist-control ventilation before and after physical therapy25 or increasing the fraction of inspired oxygen 25. In addition, mechanical ventilators allow real-time monitoring of respiratory (eg, respiratory rate or minute ventilation) and metabolic variables (eg, carbon dioxide production)22 26 that could provide useful information to individualise the dosage of physical therapy or ventilatory support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proportional modes of assisted ventilation like PAV can translate into longer and more efficient training sessions [53]. A preliminary study [72] in intubated patients showed that proportional ventilation modes such as PAV and the more recently introduced Neurally Adjusted Ventilatory Assist (NAVA) [73] during exercise resulted in higher work efficiency and less increase in oxygen consumption compared to ventilation with inspiratory pressure support [72]. Whether these results can be translated to patients with CVF is unknown.…”
Section: Potential Alternatives and Future Applicationsmentioning
confidence: 99%